CHARACTERIZATION OF THE PSYCHOMOTOR DEVELOPMENT IN CHILDREN WITH CEREBRAL PALSY WHO WERE SUBMITTED TO EQUOTHERAPY IN ANÁPOLIS -GO (Fiep Bulletin - online, 2014)
The equotherapy, that uses the horse riding in an interdisciplinary approach on health, education and riding areas, is recognized as a therapeutical method by the Federal Counsel of Medicine in Brazil since 1997. The riding re-education is indicated on the following cases: motor deficiencies caused by neuromotor lesions; cerebral lesions; neuromotor deficiencies caused by lesions on spine and orthopedic pathologies (FREIRE, 1999). The objective of this research was to characterize the psychomotor development of those who practice the equotherapy on the EMDA - Equotherapy and Multiple Deficiencies Association in Anápolis-GO. 25 patients with cerebral palsy were part of the study, from both genders, 16 men and 9 women. Psychomotor tests were done, PMB from Vitor da Fonseca (1995). The training sessions consisted on two times in a week each one of 40 minutes. The statistical analysis was the descriptive one and to compare the moments the test "t" student was used. The results were: in tonicity the children had a significant improvement (p=0,000), initially they were on the praxis profile with an unperfected movement realization, and after they passed to the dyspraxic profile. In equilibrium, children had a significant improvement (p=0,000), because before the training they showed to be in the dyspraxic profile , with difficulties on the movement, but being considered satisfying and, after the equotherapy, they moved to the eupraxic profile with an appropriate realization being classified as good. In laterality, the children obtained with the training a significant improvement (p=0,022), but it didn't change the psychomotor profile, they were in the dyspraxic profile all the time. On the body notion, the children showed an imperfect notion and uncompleted knowledge of their bodies. They had a significant improvement (p=0,003), but they couldn't change their profile. On the global praxis, the children kept the same apraxic profile, but they had, anyway, a significant improvement (p=0,005). On the thin praxis, there was a significant improvement (p=0,003), but not enough to change the psychomotor profile. The children initiated and finished the training on the apraxic profile, being considered weak. It can be concluded that equotherapy training showed results with significant changing on the psychomotor valuated areas, even that some profiles didn't change. The equotherapy can support the development on children's psychomotor areas, and by this way they can have a contribution for their life improvement.